Cracking the egg: An insight into egg hypersensitivity. Issue 2 (August 2015) - Dhanapala, Pathum; De Silva, Chamika; Doran, Tim; Suphioglu, Cenk
Highlights: Egg allergy is the second most common food allergy in children, next to cow's milk allergy. Egg allergy is mainly caused by hypersensitivity to four allergens found in the egg white. Egg yolk specific allergens may play a crucial role in the overall egg allergic reaction. Currently there is no permanent cure for egg allergy. An understanding of egg allergens and their prevalence is important for diagnosis and treatment. Abstract: Hypersensitivity to the chicken egg is a widespread disorder mainly affecting 1–2% of children worldwide. It is the second most common food allergy in children, next to cow's milk allergy. Egg allergy is mainly caused by hypersensitivity to four allergens found in the egg white; ovomucoid, ovalbumin, ovotransferrin and lysozyme. However, some research suggests the involvement of allergens exclusively found in the egg yolk such as chicken serum albumin and YGP42, which may play a crucial role in the overall reaction. In egg allergic individuals, these allergens cause conditions such as itching, atopic dermatitis, bronchial asthma, vomiting, rhinitis, conjunctivitis, laryngeal oedema and chronic urticaria, and anaphylaxis. Currently there is no permanent cure for egg allergy. Upon positive diagnosis for egg allergy, strict dietary avoidance of eggs and products containing traces of eggs is the most effective way of avoiding future hypersensitivity reactions. However, it is difficult to fully avoid eggs since they are found in a range of processed food products. An understanding of the mechanisms of allergic reactions, egg allergens and their prevalence, egg allergy diagnosis and current treatment strategies are important for future studies. This review addresses these topics and discusses both egg white and egg yolk allergy as a whole.